2012
DOI: 10.1111/j.1460-9568.2012.08229.x
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol prevents CA1 neurons against ischemic injury by parallel modulation of both GSK‐3β and CREB through PI3‐K/Akt pathways

Abstract: Accumulating evidence indicates that resveratrol potently protects against cerebral ischemia damage due to its oxygen free radicals scavenging and antioxidant properties. However, cellular mechanisms that may underlie the neuroprotective effects of resveratrol in brain ischemia are not fully understood yet. This study aimed to investigate the potential association between the neuroprotective effect of resveratrol and the apoptosis/survival signaling pathways, in particular the glycogen synthase kinase 3 (GSK-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 46 publications
1
50
0
Order By: Relevance
“…Berberine ameliorates cartilage degeneration in IL-1β-stimulated rat chondrocytes and in a rat model of OA via AKT signaling [29]. It has been reported that AKT signaling is one crucial upstream signaling pathway for CREB expression [37,38]. In this study, we investigated whether LF required the AKT signaling pathway for the activation of CREB.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Berberine ameliorates cartilage degeneration in IL-1β-stimulated rat chondrocytes and in a rat model of OA via AKT signaling [29]. It has been reported that AKT signaling is one crucial upstream signaling pathway for CREB expression [37,38]. In this study, we investigated whether LF required the AKT signaling pathway for the activation of CREB.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Several studies showed that resveratrol has the potential to defend neurons against oxidative assaults induced by a spectrum of treatments, including neurotoxins (Wu et al 2013;Renaud et al 2014) and cerebral ischemic injury (Simao et al 2012). Resveratrol plays a protective role in several neurodegenerative diseases, including PD, Alzheimer's disease (AD), and Huntington's disease (Albani et al 2010), as well as against neuroinflammation (Foti Cuzzola et al 2011).…”
mentioning
confidence: 99%
“…An element that directly controls CREB activity and cell survival is the protein kinase AKT. 44,45 We showed here that NO/cGKII directly influenced nuclear AKT localization in E6 and E8 retinal neurons. Interestingly, NO/cGKII-dependent neuronal death or survival was directly associated with an AKT-regulated CREB activation in the nucleus.…”
Section: Discussionmentioning
confidence: 67%
“…[41][42][43] In different neuronal paradigms, AKT-dependent survival may rely on downstream CREB activity in the nucleus. 44,45 Furthermore, it has been reported that NO regulates AKT activation and nuclear translocation via cGKII in retinal neurons. 22 We then decided to evaluate the role played by AKT in CREB phosphorylation regulated by cGKII in the nuclei.…”
Section: Resultsmentioning
confidence: 99%